Teaching tradition : investigating potential teaching tools for the preservation of Kyrgyz textiles traditions : a thesis presented in partial fulfilment of the requirements for the degree of Master of Design in Textiles at Massey University, Wellington, New Zealand - Rosenthal, Jennifer (Massey University, 2010)
No abstract available
Keywords: Kyrgyz; Textile design; Traditional crafts; International development; Women's handicraft cooperative; Wool felt; Instructional design